2021
DOI: 10.1016/j.bjid.2021.101617
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on income, prevention attitudes, and access to healthcare among male clients in a Sexually Transmitted Infections clinic

Abstract: Background Mobility restrictions and overloaded health services during the COVID-19 pandemic compromised services dedicated to the prevention and care of HIV and other sexually transmitted infections (STI). In this study, we present client's responses to standardized questionnaires applied during the COVID-19 pandemic period as part of the strategy to measure impacts on social and sexual vulnerability, access to STI prevention services, and access to STI care. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 31 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Routine sexual health screening decreased during the COVID-19 pandemic worldwide. [13][14][15][16] In Australia, a study from Melbourne showed a 68% reduction in asymptomatic screening related to COVID. 16 In our study, CT and NG testing dropped by 30% and 23% respectively during COVID-19.…”
Section: Testingmentioning
confidence: 99%
“…Routine sexual health screening decreased during the COVID-19 pandemic worldwide. [13][14][15][16] In Australia, a study from Melbourne showed a 68% reduction in asymptomatic screening related to COVID. 16 In our study, CT and NG testing dropped by 30% and 23% respectively during COVID-19.…”
Section: Testingmentioning
confidence: 99%
“…Other research on condom use during the pandemic is inconsistent, with some studies showing lower prevalence of condom use during the pandemic,4 9 12 13 and others showing no change 10 11 14–16. Our primary results suggest that condom use may be resilient to the deep societal changes of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 54%
“…We used Poisson regression to calculate unadjusted, survey-weighted prevalence ratios (PRs) comparing prevalence of condom use during the two time periods, and we also calculated PRs adjusted for age, income, rurality, health insurance status, relationship status and children present in the home. These factors were selected a priori based on previous studies 9 10 13 16. We assessed potential effect modification by rurality and HIV risk behaviour using an alpha level of 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations